Deteksi Gelatin Babi pada Sampel Permen Lunak Jelly Menggunakan Metode Fourier Transform Infra Red (FTIR) dan Kemometrik (Detection of Porcine Gelatin in Jelly Soft Candy Sample Using Fourier Transform Infra Red and Chemometrics) - Annisa Rahmawati; Bambang Kuswandi; Yuni Retnaningtyas (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Gelatin is widely used in some food products as gelling agent, including jelly soft candy. Most of commercial gelatin is derived from pork skin. Islam prohibits their followers to consume any food products containing pig derivates, including porcine gelatin. Therefore, it is necessary to develop some rapid and reliable methods for detection of porcine gelatin in jelly soft candy. FTIR method combined with chemometrics were chosen because it is rapid, easy and reliable. The purpose of this study was to classify of porcine gelatin in jelly soft candy using FTIR method combined with multivariate statistical methods (chemometrics). The classification method of chemometrics used to test porcine gelatin in commercial product of jelly soft candy was succesful and also in a good assessment with Xematest Pork. Keywords: bovine gelatin, jelly soft candy, porcine gelatin, FTIR, chemometrics.